A runner's high : my life in motion - Karnazes, Dean, 1962- (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"New York Times bestselling author Dean Karnazes was named by TIME magazine as one of the Hundred Most Influential People in the World. An ultramarathoning legend, Karnazes has raced and competed across the globe, from the heat of Death Valley to the frigid cold of the South Point. He once ran 50 marathons, in all 50 states, in 50 consecutive days. He's run for hundreds of hours without rest and was called a real superhero by Stan Lee. In A Runner's High, Karnazes chronicles his return to the Western States 100-Mile Endurance Run in his mid-50's after first completing the race decades ago. The Western States is infamous for its rugged and remote terrain and extreme temperatures, and becomes one the most demanding competitions of Karnazes's life, a physical and emotional reckoning with himself and what it means to stay true to one's purpose, mile after mile. Confronting his age, his career path, and his life choices, we see Karnazes as we never have before. In the end, there is no end. He lives for the journey. For Karnazes, the running experience is about the runner and the trail. It is not the sum of achievements but a story that continues to be told each day, with each step. A Runner's High is at once a page-turning adventure and a love letter to the sport from one of its most celebrated ambassadors"--